The Effect of Speed Play Training Method on Improving Cardiovascular Endurance of Pencak Silat Athletes Single Art Category - Alya Sabrina Mujakirahmah; Dikdik Zafar Sidik; Oktoviana Nur Ajid (Journal of Physical Education Health and Sport, 2025)
This study aims to determine the effect of the speed play training method on increasing cardiovascular endurance (VO₂max) in pencak silat athletes of the single arts category. Using a pretest-posttest control group design, ten athletes were divided into experimental and control groups. The experimental group received a structured speed play training program for eight sessions, while the control group followed their regular training routines. The Beep Test was used as the primary instrument to estimate VO₂max. The results of the independent t-test showed a significant difference between the groups (p = 0.044), with an average VO₂max increase of 1.04 points in the experimental group. These findings suggest that speed play is effective in improving aerobic capacity, especially due to its varied intensity patterns that match the dynamic and uninterrupted demands of single arts performances. The study also provides evidence that speed play can serve as a specific training model for pencak silat art athletes and offers recommendations for further research involving more diverse participants and physiological indicators.